In A Tertiary Care Hospital, the Use of A Postpartum Intrauterine Contraceptive Device as A Method of Contraception - Shazia Ashraf, Munazzah Bashir, Rubina Tazayyen Yousaf (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was to assess the acceptability, safety, and efficacy of a post-partum intrauterine contraceptive device among patients. Study Design: Prospective observational study Place and Duration: AIMC / Jinnah Hospital, Lahore for the duration from January 2022 to August 2022. Methods: Total 190 pregnant women of age 18-42 years were presented in this study. After receiving informed written consent, gestational age, BMI, parity, socioeconomic status, and age were determined. All the patients received postpartum intrauterine contraceptive device (PPIUCD) either of normal vaginal delivery or C-section. Outcomes were assessed in terms of safety and efficacy among all cases. Frequency of complications among all cases were assessed. Results: There were 125 (65.8%) cases had age 18-30 years and 65 (34.2%) females had age 31-42 years. 110 (57.9%) cases had BMI <25kg/m2 and 80 (42.1%) females had BMI >25kg/m2. Majority of the females 145 (76.3%) were multigravida. Mean gestational age of the females was 37.2±13.89 weeks. There were 95 (50%) cases had poor socio-economic status. We inserted PPIUD in 128 (67.4%) cases of vaginal delivery and 62 (32.6%) cases of C-section after delivery. Adverse outcomes were found in 16 (8.4%) cases in which 4 cases were of expulsion of PPIUD, heavy vaginal bleeding in 9 females and 3 cases had infection. There was no any case found of perforation among all cases. Conclusion: In this study, we came to the conclusion that postpartum implantation of an intrauterine contraceptive device is an efficient, secure, reversible, and long-acting form of contraception. Keywords: PPIUCD, Normal Delivery, C-section, Complications